Optimalisasi Pengelolaan Sampah Melalui Pelatihan Pembuatan Pupuk Kompos Organik Di Desa Mrican - Adinda Kusuma Wardani; Anton Winaryo; Arta Ekayanti; Binti Rohani; Erika Puji Astuti; Hananda Luthfi Juwariyah; Hasanah Ahlaqul Karimah; Helen Candra Puspita Dewi; Imam Sa’id Nurfrendi; Kaneisya Hokia Alfitri; Shintya Ayu Setyawati (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The problem of waste accumulation in Mrican Village, Ponorogo Regency, Indonesia, has become a big challenge for the local community. The ever-increasing waste has caused significant impacts on the environment, such as soil, water and air pollution. The government has made efforts to reduce waste by processing it into alternative fuel, but this innovation did not last long.  To overcome this problem, the Mathematics Community Research (MCR) Student Organization Capacity Strengthening (PPK ORMAWA) team at Muhammadiyah University of Ponorogo developed an innovative solution in the form of a Digital Waste House Based on the Zerowastemate Application. This concept aims to make it easier to manage waste efficiently and sustainably, starting from the household scale. Through this application, people can easily manage their waste, both in sorting, processing and data collection.